Cooperative Caching in Two-Layer Hierarchical Cache-aided Systems - Hoang, Van Xiem (H. : ĐHQGHN, 2019)
Caching has received much attention as a promising technique to overcome high data rate and stringent latency requirements in the future wireless networks. The premise of caching technique is to prefetch most popular contents closer to end users in local cache of edge nodes, e.g., base station (BS). When a user requests a content that is available in the cache, it can be served directly without being sent from the core network. In this paper, we investigat e the performance of hierarchical caching systems, in which both BS and end users are equipped with a storage memory. In particular, we propose a novel cooperative caching scheme that jointly optimizes the content placement at the BS’s and users’ caches. The proposed caching scheme is analytically shown to achieve a larger global caching gain than the reference in both uncoded - and coded caching strategies. Finally, numerical results are presented to demonstrate the effectiveness of our proposed caching algorithm